The millipede family Striariidae Bollman, 1893. VIII. Three new genera and four new species of minute millipedes from Oregon and Washington, USA(Diplopoda, Chordeumatida, Striarioidea) - Shear, William A.; Marek, Paul E. (Zootaxa, 2023)
We describe three new genera and four new species of small, litter-dwelling millipedes from the states of Oregon and Washington, USA: Miniaria ramifera, n. gen., n. sp., Miniaria richarti, n. gen., n. sp., Tigraria oregonensis, n. gen., n. sp., and Kingaria prattensis, n. gen., n. sp. Some of the unusual characters of these species are discussed, including a new type of sensory array on the third tarsus of males and a newly observed mandibular gland.